Microsurgical treatment of cerebrospinal fluid rhinorrhea in sphenoidal sinus - 崔景余 吴安华 张世刚 秦晓飞 王运杰 (Chinese journal of traumatology, 2010)
Objective：To explore the clinical manifestation,diagnosis and surgical treatment of cerebrospinal fluid rhinorrhea in sphenoidal sinus.Methods： Nine cases of cerebrospinal fluid rhinorrhea in spenoidal sinus from 2007 to 2009 were retrospectivelyanalyzed consisting of their possible etiological factors,clinical manifestations, localization of the leakage site and treatment methods. Among them, there were 3 cases of traumatic rhinorrhea, 4 postoperative rhinorrhea and 2 spontaneous rhinorrhea. All 9 patients underwent 3-dimensional CT scan in sellar region including all para-nasal sinus. Leakage site was identified and repairing procedure was performed through trans-sphenoidal approach.Results：All cases were cured with the trans-sphenoidal microsurgical procedure. They were followed up for 9 months to 2 years. No recurrence, no infection and epilepsy complications were observed.Conclusion：For the cerebrospinal fluid rhinorrhea at sphenoidal sinus, it is critical to identify the leakage site accurately and the trans-sphenoidal approach is a microinvasive and effective way to repair the leakage, which is worthy to be advocated.